True blood. The complete third season - Ball, Alan, 1957-; Paquin, Anna.; Kwanten, Ryan, 1976-; Moyer, Stephen; Harris, Charlaine; HBO Home Entertainment (Firm); HBO Entertainment (Firm); Warner Home Video (Firm) ([New York] : HBO Home Entertainment ; Burbank, Calif. : Distributed by Warner Home Video, 2011)
The Maenadian reign of terror may be over, but Sookie Stackhouse and the townspeople of Bon Temps face a new calamity that makes the bacchanalian evils of Maryanne Forrester seem tame by comparison. Sookie desperately tries to locate her fiance, ending up in a netherworld of human and undead interlopers, among them the powerful Vampire King of Mississippi, Russell Edgington.
Bad blood -- Beautifully broken -- It hurts me too -- 9 crimes -- Trouble -- I got a right to sing the blues -- Hitting the ground -- Night on the sun -- Everything is broken -- I smell a rat -- Fresh blood -- Evil is going on.
Based on the Sookie Stackhouse novels by Charlaine Harris.
Anna Paquin, Ryan Kwanten, Stephen Moyer.
Originally broadcast as single episodes of a television series in 2010.
Rating: TV-MA CHV rating: 18A.
DVD, widescreen presentation; Dolby Digital 5.1 or 2.0 (Spanish).
English, French or Spanish dialogue; English, French, Portuguese or Spanish subtitles. Subtitled for the deaf and hard of hearing.
Keywords: Stackhouse, Sookie (Fictitious character) -- Drama; Vampires -- Louisiana -- Drama; Waitresses -- Louisiana -- Drama; Bars (Drinking establishments) -- Louisiana -- Drama; Blood -- Drama; Man-woman relationships -- Louisiana -- Drama; Fantasy television programs; Horror television programs; Video recordings for the hearing impaired; Television programs; Vampire television programs; Thrillers (Television programs); Horror television programs